An Open Labelled Randomized Controlled Parallel Group Clinical Study to Evaluate the Efficacy of Prasarini Sandhanam in Management of Rheumatoid Arthritis - Nagendra, Ramyashree; Gopala , Krishna G (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Rheumatoid Arthritis (RA) is a chronic inflammatory disease of unknown aetiology marked by a symmetric, peripheral polyarthritis. The prevalence of Rheumatoid arthritis is approximately 0.8 – 1.0 % in Indian subcontinent, with female to male ratio of 3:1. In Ayurveda, Amavata can be co-related to Rheumatoid arthritis based on its clinical signs and symptoms. Mandagni (hypo functioning of digestive fire) and derangement in Vata (vital force of the body) results in manifestation RA. Aims and Objectives: To evaluate the efficacy of Prasarini Sandhanam (PS) and Simhanada Guggulu (SNG) and compare their efficacies in management of Rheumatoid Arthritis. Materials and methods: In the present study 32 patients were enrolled and the study was completed in 30 patients. The patients were allocated randomly in two groups. Group A was administered with SNG (control group) while Group B was administered with PS (trial group). Results: The effect of treatment on 30th day has shown statistically significant result in group A with p value <0.05 in parameters like pain, stiffness, swelling and warmth in the joints, general signs and symptoms and degree of disease activity score. The effect of treatment in group A did not show statistically significant result in General functional capacity, tenderness in joints and Quality of life of patients through Barthel’s index score with p value > 0.05. On follow up all parameters did not show statistical significance with p value > 0.05. The effect of PS in group B on 30th day have shown statistically highly significant result with p value <0.01 in all parameters whereas on follow up it did not show statistically significant result with p value > 0.05 in all parameters. On comparison, Group B have shown better results than Group A in all the parameters. =Conclusion: Both the groups showed statistically significant results but on comparison group B (PS) showed better results than group A (SNG). By the virtue of its aetiology, pathogenesis, clinical signs and symptoms and management, Rheumatoid arthritis bears close resemblance to Amavata and can be tackled effectively on the lines of its management as mentioned in classics.